Mathematics and computation in music : 7th international conference, MCM 2019, Madrid, Spain, June 18–21, 2019, proceedings /: 7th international conference, MCM 2019, Madrid, Spain, June 18–21, 2019, proceedings. (2019) - Unknown
No abstract available